Theoretical and Experimental Study of Optical Response of Bimetallic Platinum and Gold Nanoparticles: Nanoalloys and Core/Shell Configurations - Mani Gonzalez, Pierre Giovanni (2021)
In this research, a theoretical and experimental study of bimetallic gold and platinum nanoparticles is reported. From the green synthesis approach, a combination of rongalite with sucrose is used as a reducing and stabilizing agent. Nanoalloys (Au@ Pt) and Pt-core/Au-shell nanoparticles were obtained according to the synthesis process used, and the optical response was analyzed. For nanoalloys, two absorption bands were associated with localized surface plasmon resonances. These were located at 300 nm and another between 350 nm and 365 nm, respectively. For core/shell type nanoparticles, an absorption band centered at 530 nm was observed. The images obtained by transmission electronic microscopy (TEM) confirmed the presence of quasi-spherical nanoparticles with core/shell type configurations. Numerical calculations of the cross sections for a Pt-core/Au-shell nanoparticle with spherical …